Sistem Pendukung Keputusan (SPK) Menentukan Kelayakan Calon Penerima Zakat Menerapkan Multi-Factor Evaluation Process (MFEP) - Iis Afrianty; Ravi Umbara (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
Zakat is one of the pillars of Islam which must be met and some muzaki entrust distribution of zakat in a National Zakat Organization (LAZNAS). Zakat collected in LAZNAS then channeled to mustahik (receive zakat) eligible in accordance with the applicable syar'i. Problems arise when determining the eligibility of candidates because the number of the lot and extends over a period of time so require accuracy in the selection. In this study constructed a Decision Support System (DSS) for selecting candidates using the Multi-Factor Evaluation Process (MFEP). The data used are the criteria and sub-criteria, as well as potential recipients (alternative data). The criteria used are five criteria (the condition of the ability of households, income and dependents, residence, ownership of the goods, and character). At each criterion has sub-criteria with a total of 35 sub-criteria, each of which has a weight value and sub-criteria used in the calculation MFEP. The result of the calculation resulted in a total weight of weight evaluation of each alternative in the form of ranking. Based on testing, black box the system was as expected while testing the User Acceptance Test using a Likert scale by distributing questionnaires, giving a value of testing 87.87% (system are received is very good). Therefore, it can be concluded that the system has been built with MFEP can be applied to the case of recipients of zakat. Keywords: Decision Support System, Multi-Factor Evaluation Process, ranking, zakat